Inteligencja interpersonalna : tworzenie i utrzymywanie solidnych relacji zawodowych (Report (Center for Creative Leadership), 2018)
Having interpersonal skills will allow you to motivate, inspire, and successfully lead others, as well as further your own career development. This guidebook will show you how, through self-awareness and strategic implementation of behaviors, you can utilize interpersonal savvy to make the most out of negative situations, develop and lead others, and create a positive working environment despite daily challenges and hardships.